1962
DOI: 10.1002/macp.1962.020560116
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline polymers of phenyl‐ and n‐butylisocyanates

Abstract: By polymerizing phenyl or n‐butyl isocyanate in various solvents in the presence of anionic catalysts such as lithium or sodium alkyls, crystalline polymers were obtained. For both polymers, the I.R. spectra, the X‐ray diffraction spectra and other physical properties are reported. The possible structures of the two crystalline polymers are discussed. By cationic catalysts (e.g. AlBr3) amorphous polymers were obtained from phenylisocyanate, but no polymers from n‐butylisocyanate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1963
1963
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…Sobue et al [10], however, obtained two very different spectra for polybutyl isocyanate according to the method of preparation. Irradiation of monomer in the solid state produced a polymer with a spectrum almost identical with that published by other workers using anionic initiators [4,17]. The product from liquid phase irradiation, while still showing the carbonyl absorption band, was entirely different in other respects.…”
Section: A Spectroscopic Evidencesupporting
confidence: 54%
See 2 more Smart Citations
“…Sobue et al [10], however, obtained two very different spectra for polybutyl isocyanate according to the method of preparation. Irradiation of monomer in the solid state produced a polymer with a spectrum almost identical with that published by other workers using anionic initiators [4,17]. The product from liquid phase irradiation, while still showing the carbonyl absorption band, was entirely different in other respects.…”
Section: A Spectroscopic Evidencesupporting
confidence: 54%
“…X-ray diffraction studies on films of Shashoua's original polymers indicated a low order of crystallinity for most polyalkyl isocyanates, but a high order for polyallyl isocyanate. In 1962 Natta et al [4] prepared polybutyl isocyanate with ethyllithium in benzene and found a high order BERGER of crystallinity compared with the product made by Shashoua's method with sodium cyanide in DMF. The results implied that the former catalyst gave rise to a more regular chemical structure than the latter which could, according to these observations, have contained substantial quantities of both amide and acetal structure.…”
Section: Linear Diisocyanatesmentioning
confidence: 95%
See 1 more Smart Citation
“…All alkyl nylon-1 polymers, with the exception of poly(allyl isocyanate), have a low order of crystallinity as shown by X-ray diffraction. However, the polymerization of n-butyl isocyanate and phenyl isocyanate in various solvents at −78 • C, initiated by lithium or sodium alkyls, produces crystalline polymers (28). The mechanism of the sodium cyanide catalyzed polymerization in DMF involves intermediates having a spiro structure (29).…”
Section: Homopolymerizationmentioning
confidence: 99%
“…Natta et al have prepared crystalline 1-nylons of phenyl and n-butyl isocyanates. 2 The first attempts to copolymerize isocyanates with vinyl monomers were the subjects of patent applications. The first, by Furukawa and co-~orkers,~ alleged copolymerization by addition of various initiators to mixtures of vinyl monomers and diisocyanates in the temperature range of -78 to 60°C and reported obtaining insoluble, infusible products.…”
Section: Introductionmentioning
confidence: 99%